2010
DOI: 10.2215/cjn.08511109
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Hyperfiltration in Adult Sickle Cell Anemia

Abstract: Background and objectives: Sickle cell anemia-associated nephropathy is a growing matter of concern because renal failure affects most aging sickle cell anemia patients. Glomerular damage is a common feature revealed by a microalbuminuria or a macroalbuminuria. Although glomerular hyperfiltration has been described for decades in this population, its prevalence in young adults is unknown.Design, setting, participants, & measurements: To address this issue, as well as the clinical and biologic correlates of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
148
3
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(168 citation statements)
references
References 31 publications
12
148
3
5
Order By: Relevance
“…cFGF23 correlated negatively with hemoglobin and positively with GFR, suggesting that cFGF23 concentration correlates with the consequences of the SCD, anemia and glomerular hyperfiltration that is an early marker of SCD renal dysfunction. 8 In the present study, FGF23 elevation was not due to a decrease in GFR. Release of phosphate by hemolysis might have stimulated FGF23 release.…”
supporting
confidence: 45%
“…cFGF23 correlated negatively with hemoglobin and positively with GFR, suggesting that cFGF23 concentration correlates with the consequences of the SCD, anemia and glomerular hyperfiltration that is an early marker of SCD renal dysfunction. 8 In the present study, FGF23 elevation was not due to a decrease in GFR. Release of phosphate by hemolysis might have stimulated FGF23 release.…”
supporting
confidence: 45%
“…They found that eGFR using the MDRD formula was a robust predictor of hyperfiltration when compared to the actual GFR. 15 Although our data have confirmed the downward trend of eGFR and upward trend of ACR as patients age, the exact temporal and pathological relationship between these two factors has not been fully investigated in individual patients, and further prospective studies are needed. The use of angiotensin-converting enzyme (ACE) inhibiting medications has been shown to reduce levels of proteinuria in small-scale trials and may prove to be beneficial in delaying the onset of CKD.…”
Section: Tg Day Et Almentioning
confidence: 50%
“…5,13 Similar studies in adults, however, have not replicated this finding, although an association between low hemoglobin levels and hyperfiltration have been reported. [14][15] More recently, Maier-Redelsperger et al utilized a marker of red cell survival derived from mature red blood cell hemoglobin (RBC Hb) and reticulocyte hemoglobin (RET Hb), and showed that the log (RBC Hb/RET Hb) was highly correlated with LDH, bilirubin and albuminuria. 16 In the present study, we have carried out a retrospective investigation of the prevalence of albuminuria and hyperfiltration in a larger cohort of adults with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…While, renal replacement therapy with hemodialysis can extend survival, the start of dialysis is a poor prognostic factor with 1-year mortality of 26% [14,110]. Glomerular hypertension and hyper-filtration are characteristic of early sickle cell glomerulopathy, and albuminuria is its earliest clinical correlate [111][112][113]. Repeated cycles of sickling are thought to cause microinfarctions and renal medullary ischemia [114,115].…”
Section: Pulmonary Complicationsmentioning
confidence: 99%